The Role of Emotional Intelligence among Adolescents in Anxiety and Depression: Exploring the Relationship between Emotional Intelligence, Anxiety, and Depression among Adolescents (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The association between emotional intelligence, anxiety and depression among teenagers was explored in this research. In the adolescent community, elevated anxiety and depression are frequently found, and if kept unchecked, it may have long-term detrimental effects that impair educational success and a number of significant life outcomes. Decreased anxiety and depression have been correlated with the usage of mindfulness strategies, but the basic reasons behind this are still starting to be recognized. Previous adult sample study has proposed that the production of emotional intelligence (EI) could be one pathway by which mindfulness confers its well-being benefits. This report is the first to investigate the relationship in an adolescent community between mindfulness, EI, anxiety, and depression.